2018
DOI: 10.1001/jamanetworkopen.2018.1079
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated With Major Cardiovascular Events 1 Year After Acute Myocardial Infarction

Abstract: Key Points Question What are the risk factors associated with major cardiovascular events within 1 year among patients who survive an acute myocardial infarction? Findings In this cohort study of 4227 patients with acute myocardial infarction, 19 risk factors associated with major cardiovascular events 1 year after acute myocardial infarction, comprising 15 unique variables, were identified. A risk model to predict 1-year cardiovascular events after an acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 38 publications
0
47
0
Order By: Relevance
“…Although there have been dramatic improvements in public health that have spurred a decline in CVD related deaths over the past several decades, incidence of CVD mortality has remained steady in recent years. As a result, considerable effort has been placed in improving risk prediction of CVD-related events [2,3]. Despite this, clinical practice has remained largely unchanged, relying on traditional scoring metrics such as Thrombolysis in Myocardial Infarction (TIMI) Risk Score [4] for risk stratification.…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been dramatic improvements in public health that have spurred a decline in CVD related deaths over the past several decades, incidence of CVD mortality has remained steady in recent years. As a result, considerable effort has been placed in improving risk prediction of CVD-related events [2,3]. Despite this, clinical practice has remained largely unchanged, relying on traditional scoring metrics such as Thrombolysis in Myocardial Infarction (TIMI) Risk Score [4] for risk stratification.…”
Section: Introductionmentioning
confidence: 99%
“…In another study the mean (SD) age of the cohort was found as 60.8+11.8 years and 994 of 4227 patients (23.5%) were female (Wang et al 2018). 14 In this study the prevalence rate of major risk factors of cardiovascular disease was found as obesity 32.5%, smoking 18.0%, diabetes 6.1% and hypertension 29.0%. Another study conducted in residents of Saronikos municipality (Attica region) in 2014 found the prevalence of major risk factors as obesity 21.6%, current smoking 38.9%, diabetes 11.1%, and hypertension 28.8%.…”
Section: Discussionmentioning
confidence: 55%
“…We fit a logistic model with Markov Chain Monte Carlo (MCMC) simulation using the training cohort that containing all candidate risk factors. Subsequently, a posterior probability for each factor was further calculated to assess the association strength between risk factor and the clinical outcome [14,15]. Generally, the factor with a posterior probability > 0.95 (or < 0.05 for factors with estimates < 0.0) was thought to be significant for predicting the prognosis and finally included in the risk factor list [16].…”
Section: Statistical Analyses Risk Factor Selection and Evaluationmentioning
confidence: 99%
“…Further, data from training group were used to evaluate the selected risk factors. Latent class analysis was conducted by an unsupervised machine learning algorithm that does not require an outcome [14]. Generally, if the selected risk factors are significantly associated with the clinical outcome, they will have the ability to assign patients to risk class with unsupervised learning algorithms.…”
Section: Statistical Analyses Risk Factor Selection and Evaluationmentioning
confidence: 99%